Da despersonalização à impessoalidade na poesia de Ana Cristina Cesar - Lima, Dhandara Soares de (2013)
The concept of poetic impersonality was widely spread in literature starting at the beginning of the twentieth century. Considering that meaning and aesthetical intention of the impersonal poetry can vary, according to theoretical guidance adopted, in this work we have used the concepts of Impersonality and Depersonalization as theorized and practiced by Thomas Stearns Eliot (1888-1968), recognized English language author, whose work met great and immediate repercussion and influenced his generation and subsequent artists and by Fernando Pessoa (1888-1935), poet of great importance to the Portuguese language literature, who, as shown by previous researches, presents aesthetical work similar to the English language author s. In this work, we have listed the main points in which these authors concepts of poetic making distancing between personality and poetic voice are similar. Through this research, we have attempted to demonstrate that (1) the author Ana Cristina Cesar shared the aesthetic concepts of Eliot s and Pessoa s, presenting similar ideas to the ones listed and fundamental to the authors we have chosen; and (2) Cesar s poetic work presents similar characteristics of poetic depersonalization found in Pessoa s and Eliot s work, characterizing it as impersonal. Thus, our object is not only to investigate this important poet of Brazilian literature, but mainly demonstrated how she continues the aesthetic project of impersonallity developed and theorized by the authors cited, and, in a general manner, distancing between the author s personality and the poetic voice